Host Epac1 is required for cAMP-mediated invasion by Trypanosoma cruzi - Musikant, Alejandro Daniel (2017)
Mechanistic details of the modulation by cAMP of Trypanosoma cruzi host cell invasion remain ill-defined. Here we report that activation of host's Epac1 stimulated invasion, whereas specific pharmacological inhibition or maneuvers that alter Epac1 subcellular localization significantly reduced invasion. Furthermore, while specific activation of host cell PKA showed no effect, its inhibition resulted in an increased invasion, revealing a crosstalk between the PKA and Epac signaling pathways during the process of invasion. Therefore, our data suggests that subcellular localization of Epac might be playing an important role during invasion and that specific activation of the host cell cAMP/Epac1 pathway is required for cAMP-mediated invasion.